Bald Eagle Search Algorithm for Parameter Identification of Proton Exchange Membrane Fuel Cell - Yang, Bo; Li, Danyang; Zeng, Chunyuan; Han, Yiming; Li, Junhui (Frontiers in Energy Research, 2022)
A precise and reliable proton exchange membrane fuel cell (PEMFC) parameter identification performs an essential function in simulation analysis, optimal control, and performance research of actual PEMFC systems. Unfortunately, achieving an accurate, efficient, and stable parameter identification can sometimes be proven problematic for traditional optimization methods, owing to its strong coupling, inherent nonlinear, and multi-variable characteristics. Therefore, an advanced bald eagle search (BES) algorithm is designed to dependably identify the unknown parameters of electrochemical PEMFC model in this work. In the purpose of evaluating and analyzing the overall optimization performance of the BES comprehensively, it is compared with genetic algorithm (GA) based on MATLAB under two cases. The simulation results fully indicate that the precision, accuracy, and stability of optimization results can be remarkably improved through the application of BES.